2016
DOI: 10.1073/pnas.1601747113
|View full text |Cite
|
Sign up to set email alerts
|

Structural rearrangement of the intracellular domains during AMPA receptor activation

Abstract: α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) are ligand-gated ion channels that mediate the majority of fast excitatory neurotransmission in the central nervous system. Despite recent advances in structural studies of AMPARs, information about the specific conformational changes that underlie receptor function is lacking. Here, we used single and dual insertion of GFP variants at various positions in AMPAR subunits to enable measurements of conformational changes using fluorescence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 62 publications
4
49
0
Order By: Relevance
“…Desensitization after photoactivation of Y797AzF was strongly reduced. Comparing this to our recent FRET data suggesting the M4 (as assayed from the C-terminal movement) is likely to move during gating, desensitization and without pore opening (Zachariassen et al, 2016), a wider role for peripheral interactions to modulate AMPAR function appears likely. We did not detect crosslinking either within or between subunits for Y797AzF.…”
Section: Discussionsupporting
confidence: 63%
“…Desensitization after photoactivation of Y797AzF was strongly reduced. Comparing this to our recent FRET data suggesting the M4 (as assayed from the C-terminal movement) is likely to move during gating, desensitization and without pore opening (Zachariassen et al, 2016), a wider role for peripheral interactions to modulate AMPAR function appears likely. We did not detect crosslinking either within or between subunits for Y797AzF.…”
Section: Discussionsupporting
confidence: 63%
“…The emitted fluorescence was collected using a broad-band mirror and focused onto an iXon3 888 EM/CCD camera (Andor Inc., South Windsor, CT). The illuminated area on the coverslip was ~2500 µm (Zachariassen et al, 2016). A region of the oocyte was selected to focus the sample and then adjust the TIRF angle.…”
Section: Methodsmentioning
confidence: 99%
“…A common strategy to incorporate fluorophores into target proteins is the fusion to fluorescent proteins, such as GFP or one of its spectral variants (Miranda et al, 2013; Zachariassen et al, 2016). This approach has the built-in convenience of encoding but their positioning within the target protein can be limited by their large size, which may impact protein function or trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that, upon agonist binding, stabilization of the active state by TARP may be achieved, not only through extracellular interactions but also through further altering interactions within the membrane domains and even the CT. Indeed, a recent study employing dynamic spectroscopy suggested that the CT and the intracellular linker between M1 and M2 move during AMPAR activation (Zachariassen et al, 2016).…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%